KNOWLEDGE LEVEL OF DENTAL STUDENTS FKG UNBRAH ABOUT THE TREATMENT OF STAINLESS-STEEL CROWN (SSC) IN PEDIATRIC PATIENTS AT DENTAL HOSPITAL BAITURRAHMAH - Sri Pandu Pandu; Leny Sang Surya; Utami Arma; Resa Ferdina; Hanifah Maharani Al Asad (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Knowledge is the result of human sensingor the result of knowing someone about an object through the senses they have at the time. Sensing to produce knowledge is strongly influenced by the intensity of attention and perception of the object. Stainless Steel Crown (SSC) is a dental alloy (alloy) nicarat which can be used for temporary or permanent fillings in the shape of dental anatomy. The research objective was to find out the level of knowledge of professional education students about SSC in pediatric patients at RSGM Baiturrahmah . Materials and Methods: This is descriptive with a cross-sectional research design, sampling technique with total sampling. The population  was taken from 50 professional education students at RSGM Baiturrahmah who carried out stainless-steel crown treatment with univariate analysis presented in the form of frequency distribution and data processing using the computerized SPSS program version of IBM 24.0 . Results: The results of this study were obtained because they had received material about the treatment of SSC in pediatric patients and before they carried out the treatment, they had responded in advance regarding the stages of SSC treatment in pediatric patients. Conclusion: That the results are in the good category with a percentage of 98% (49 people) of the population studied